Longitudinal Multicenter Analysis of Outcomes After Cessation of Control Measures for Vancomycin-Resistant Enterococci. (2nd November 2016) - Lemieux, Camille; Gardam, Michael; Evans, Gerald; John, Michael; Suh, Kathryn N.; vanWalraven, Carl; Vicencio, Elisa; Coulby, Cameron; Roth, Virginia; Hota, Susy
Abstract : OBJECTIVE: To assess clinically relevant outcomes after complete cessation of control measures for vancomycin-resistant enterococci (VRE). DESIGN: Quasi-experimental ecological study over 3.5 years. METHODS: All VRE screening and isolation practices at 4 large academic hospitals in Ontario, Canada, were stopped on July 1, 2012. In total, 618 anonymized abstracted charts of patients with VRE-positive clinical isolates identified between July 1, 2010, and December 31, 2013, were reviewed to determine whether the case was a true VRE infection, a VRE colonization or contaminant, or a true VRE bacteremia. All deaths within 30 days of the last VRE infection were also reviewed to determine whether the death was fully or partially attributable to VRE. All-cause mortality was evaluated over the study period. Generalized estimating equation methods were used to cluster outcome rates within hospitals, and negative binomial models were created for each outcome. RESULTS: The incidence rate ratio (IRR) for VRE infections was 0.59 and the associated P value was .34. For VRE bacteremias, the IRR was 0.54 and P= .38; for all-cause mortality the IRR was 0.70 and P= .66; and for VRE attributable death, the IRR was 0.35 and P= .49. VRE control measures were not significantly associated with any of the outcomes. Rates of all outcomes appeared to increase during the 18-month period after cessation of VRE control measures, but none reached statistical significance. CONCLUSION: Clinically significant VRE outcomes remain rare. Cessation of all control measures for VRE had no significant attributable adverse clinical impact. Infect Control Hosp Epidemiol 2016;1–7